Analysis of Diversity of Food Consumption in Families of Stunting Toddlers - Suhaimi, Ahmad; Roni, Muhammad; Kusumayana, Purna (Jurnal Penelitian Pendidikan IPA, 2023)
The nutritional status of toddlers is an indicator of the diversity of family food consumption. This research aims to determine the diversity of food consumption in families of stunted toddlers and its relationship to the incidence of stunting in toddlers in Batang Alai Selatan District, Hulu Sungai Tengah Regency, South Kalimantan. This type of associative research uses primary and secondary data sourced from respondents and BPS data from Hulu Sungai Tengah Regency. This research uses analysis of food consumption patterns with the help of 24-hour food recall. The relationship between diversity in family food consumption and the incidence of stunting in children under five using Chi-square analysis. The research results show that the DDP score for food diversity for toddlers in Batang Alai Selatan District reached 77.3. The criteria for food consumption for families of children under five in the research area it still needs to be more diverse because it is still dominated by the grain food group (52.8%) and animal food (38.3%). The Chi-Square test results show that the relationship between food consumption diversity and the incidence of stunting in toddlers has an Asymp value. Sig. (2-sided) 0.000 < 0.05, the calculated Chi-Square value is 20.17 > Chi-square table 3.841, so it can be concluded that there is a significant relationship between the diversity of family food consumption and the incidence of stunting in toddlers